2017
DOI: 10.1371/journal.pcbi.1005680
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the tumor and the blood systemic response of breast cancer patients

Abstract: Although systemic immunity is critical to the process of tumor rejection, cancer research has largely focused on immune cells in the tumor microenvironment. To understand molecular changes in the patient systemic response (SR) to the presence of BC, we profiled RNA in blood and matched tumor from 173 patients. We designed a system (MIxT, Matched Interactions Across Tissues) to systematically explore and link molecular processes expressed in each tissue. MIxT confirmed that processes active in the patient SR ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 69 publications
3
26
0
Order By: Relevance
“…In a recent analysis of interactions between gene expression in BC tissues and blood samples nested in the NOWAC postgenome study, 18 we found that genes expressed in tumors and used as markers are not necessarily expressed in a similar manner in blood. Not surprisingly, tumors were enriched for genes related to cancer hallmarks, while in blood, the genes represented either general cellular or immune-related processes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a recent analysis of interactions between gene expression in BC tissues and blood samples nested in the NOWAC postgenome study, 18 we found that genes expressed in tumors and used as markers are not necessarily expressed in a similar manner in blood. Not surprisingly, tumors were enriched for genes related to cancer hallmarks, while in blood, the genes represented either general cellular or immune-related processes.…”
Section: Discussionmentioning
confidence: 85%
“… 17 Additionally, in a recent study, we compared gene expression in blood and breast tumor tissue. 18 We revealed some similarities in expression profiles mainly for immunogenic tumors; however, we demonstrated that there is no obligate common gene expression pattern.…”
Section: Introductionmentioning
confidence: 76%
“…[16], [17]). We have also used the gene expression datasets to explore gene expression signals in blood and interactions between the tumor and the blood systemic response of breast cancer patients [18], [19]. Some analyses have resulted in patents [20] and commercialization efforts.…”
Section: Data Analysis Lessons Learned In the Norwegian Women And Canmentioning
confidence: 99%
“…[5] We generated and analyzed expression profiles from blood and matched tumor cells in 173 breast cancer patients included in the Norwegian Women and Cancer (NOWAC) study. The MIxT analysis starts by identifying sets of genes tightly co-expressed across all patients in each tissue.…”
Section: Motivating Examplementioning
confidence: 99%
“…In other languages, libraries for biological bomputation are often availalbe like BioPython [2] and biogo [3] for Python or Go, respectively. Projects such as Galaxy 5 and Common Workflow Language (CWL) 6 enable resarchers to build and run biological data analysis pipelines consisting of a wide range of tools. Although these framework are tremendously helpful, we need novel approaches to build applications that integrate high-performance bioinformatics tools with specialized user-interfaces and interactive visualizations.…”
Section: Introductionmentioning
confidence: 99%